Music and SDGs for educational improvement, entrepreneurship and inclusion - Vernia Carrasco, Ana María (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
The main objective of this work was to propose a training and employability program, from art, in order to facilitate social, educational and employability inclusion in a neighborhood. The secondary objectives were to know the real human profile of a certain neighborhood in the city of Castellón. Assess the social and educational situation of the neighborhood. Assess the artistic and entrepreneurial level of the neighborhood and its interest. Connect the Sustainable Development Goal (SDG) 4 (Education). The methodology, of a mixed quantitative and qualitative nature, used a questionnaire, two interviews and a brief theoretical review.